2018
DOI: 10.1038/s41380-018-0051-3
|View full text |Cite|
|
Sign up to set email alerts
|

Striatopallidal neurons control avoidance behavior in exploratory tasks

Abstract: The dorsal striatum has been linked to decision making under conflict, but the mechanism by which striatal neurons contribute to approach-avoidance conflicts remains unclear. We hypothesized that striatopallidal dopamine D2 receptor (D2R)-expressing neurons promote avoidance, and tested this hypothesis in two exploratory approach avoidance conflict paradigms in mice: the elevated zero maze and open field. Genetic elimination of D2Rs on striatopallidal neurons (iMSNs), but not other neural populations, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…The D2 iMSN ablation also results in avoidance of anxiogenic areas, such as the open arms of an elevated zero maze or the center zone of an open field (LeBlanc et al, 2018). Low-power optogenetic stimulation of iMSNs also induced avoidance of such anxiogenic areas (LeBlanc et al, 2018). In a decision-making task, risk-avoidance behavior also appears to be controlled by accumbal iMSN activity: iMSNs activity was tuned to risky outcomes, and optogenetic activation of these neurons reduced risky actions in risk-taker rats (Zalocusky et al, 2016).…”
Section: Neuronal Ensemblesmentioning
confidence: 96%
See 1 more Smart Citation
“…The D2 iMSN ablation also results in avoidance of anxiogenic areas, such as the open arms of an elevated zero maze or the center zone of an open field (LeBlanc et al, 2018). Low-power optogenetic stimulation of iMSNs also induced avoidance of such anxiogenic areas (LeBlanc et al, 2018). In a decision-making task, risk-avoidance behavior also appears to be controlled by accumbal iMSN activity: iMSNs activity was tuned to risky outcomes, and optogenetic activation of these neurons reduced risky actions in risk-taker rats (Zalocusky et al, 2016).…”
Section: Neuronal Ensemblesmentioning
confidence: 96%
“…However, more recent work demonstrated that iMSNs have as much behavioral specificity as dMSNs in their activity patterns, making it unlikely that they are providing a blanket of inhibition over all potentially competing actions (Klaus et al, 2017;Parker et al, 2018). In addition, rather than simply inhibiting movement, iMSNs appear to promote specific behavioral strategies such as risk aversion (Zalocusky et al, 2016, Geddes et al, 2018Klaus et al, 2017;LeBlanc et al, 2018). In sum, while both pathways are coactivated during movement, the contribution of each pathway to action selection has remained difficult to clarify.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies argue that indirect pathway activity is critical for the generation of action sequences, possibly through the suppression of competing actions and termination of selected actions. Thus, D2-SPNs are recruited during natural and trained behaviours, and inhibiting them impairs action performance (Cui et al 2013;Sippy et al 2015; Barbera et al 2016;Carvalho Poyraz et al 2016;Lambot et al 2016;Lemos et al 2016;Tecuapetla et al 2016;LeBlanc et al 2018;Markowitz et al 2018). The STN is also a component of the so-called hyperdirect pathway, which rapidly relays cortical excitation to the basal ganglia output nuclei (and GPe) (Nambu et al 1996(Nambu et al , 2002Maurice et al 1999;Degos et al 2008;Tachibana et al 2008;Kita & Kita, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have demonstrated distinct electrophysiological properties in MSN subtypes that correspond to morphological properties (Ade, Janssen, Ortinski, & Vicini, 2008;Cepeda et al, 2008;Chan et al, 2012;Chuhma, Tanaka, Hen, & Rayport, 2011;Gertler, Chan, & Surmeier, 2008;Kreitzer & Malenka, 2007;Ma et al, 2013;Pascoli et al, 2014;Willett et al, 2018). These differential properties, including their projection circuitry through the brain, can often give rise to differential action, motivational, and emotional behavioral outcomes (Creed, Ntamati, Chandra, Lobo, & Luscher, 2016;Ferguson et al, 2011;Francis et al, 2015;Heinsbroek et al, 2017;Hikida, Kimura, Wada, Funabiki, & Nakanishi, 2010;Kravitz et al, 2010;Kravitz, Tye, & Kreitzer, 2012;LeBlanc et al, 2018;LeGates et al, 2018;Lobo et al, 2010;Massaly et al, 2019;Rothwell et al, 2014). These differential properties, including their projection circuitry through the brain, can often give rise to differential action, motivational, and emotional behavioral outcomes (Creed, Ntamati, Chandra, Lobo, & Luscher, 2016;Ferguson et al, 2011;Francis et al, 2015;Heinsbroek et al, 2017;Hikida, Kimura, Wada, Funabiki, & Nakanishi, 2010;Kravitz et al, 2010;Kravitz, Tye, & Kreitzer, 2012;LeBlanc et al, 2018;LeGates et al, 2018;Lobo et al, 2010;Massaly et al, 2019;Rothwell et al, 2014).…”
mentioning
confidence: 99%
“…These properties are altered in MSN subtypes in diseased states including neurodegeneration, addiction, stress-induced affective behavior, pain, and repetitive behaviors (Chen et al, 2017;Fieblinger et al, 2014;Francis et al, 2015Francis et al, , 2017Galvan, Andre, Wang, Cepeda, & Levine, 2012;Graziane et al, 2016;Hearing et al, 2016;Heinsbroek et al, 2017;Kim, Park, Lee, Park, & Kim, 2011;LeGates et al, 2018;Lim, Huang, Grueter, Rothwell, & Malenka, 2012;Massaly et al, 2019;Ren et al, 2016;Rothwell et al, 2014;Schwartz et al, 2014;Terrier, Luscher, & Pascoli, 2016). These differential properties, including their projection circuitry through the brain, can often give rise to differential action, motivational, and emotional behavioral outcomes (Creed, Ntamati, Chandra, Lobo, & Luscher, 2016;Ferguson et al, 2011;Francis et al, 2015;Heinsbroek et al, 2017;Hikida, Kimura, Wada, Funabiki, & Nakanishi, 2010;Kravitz et al, 2010;Kravitz, Tye, & Kreitzer, 2012;LeBlanc et al, 2018;LeGates et al, 2018;Lobo et al, 2010;Massaly et al, 2019;Rothwell et al, 2014). Additionally, in some of these pathological states, mitochondrial properties are disrupted in MSNs Hollis et al, 2015;Larrieu et al, 2017).…”
mentioning
confidence: 99%